2015
DOI: 10.1007/s00401-015-1519-8
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation sequencing in routine brain tumor diagnostics enables an integrated diagnosis and identifies actionable targets

Abstract: With the number of prognostic and predictive genetic markers in neuro-oncology steadily growing, the need for comprehensive molecular analysis of neuropathology samples has vastly increased. We therefore developed a customized enrichment/hybrid-capture-based next-generation sequencing (NGS) gene panel comprising the entire coding and selected intronic and promoter regions of 130 genes recurrently altered in brain tumors, allowing for the detection of single nucleotide variations, fusions, and copy number aberr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 216 publications
(189 citation statements)
references
References 29 publications
5
183
0
1
Order By: Relevance
“…2 High-throughput sequencing has made possible the ability to molecularly profile patients and tumors at time of diagnosis, thus leading to cancer diagnoses and treatment beyond histopathology and traditional, standard-ofcare therapies. 3,4 Genomic profiling has been carried out across a multitude of pediatric CNS tumors, revealing targetable driver mutations and molecularly distinct tumor subtypes. 5 Certainly, medulloblastoma is a prime example of how molecular profiling has improved risk stratification, prognostic prediction, and focused treatment strategies.…”
Section: Abstract Molecular Profiling | Next-generation Sequencing |mentioning
confidence: 99%
See 1 more Smart Citation
“…2 High-throughput sequencing has made possible the ability to molecularly profile patients and tumors at time of diagnosis, thus leading to cancer diagnoses and treatment beyond histopathology and traditional, standard-ofcare therapies. 3,4 Genomic profiling has been carried out across a multitude of pediatric CNS tumors, revealing targetable driver mutations and molecularly distinct tumor subtypes. 5 Certainly, medulloblastoma is a prime example of how molecular profiling has improved risk stratification, prognostic prediction, and focused treatment strategies.…”
Section: Abstract Molecular Profiling | Next-generation Sequencing |mentioning
confidence: 99%
“…8 With these advancements, institutions are working to incorporate genomic profiling into routine patient care to improve diagnostic accuracy, better predict outcome, and personalize therapy. 3,4 Our medical center is implementing these techniques in the pediatric neuro-oncology population and now has a year of practice in doing so. Herein we describe our experience using next-generation sequencing to diagnose and treat children with a variety of brain tumors and document how genomic profiling has significantly augmented the comprehensive nature of our treatment strategy.…”
Section: Abstract Molecular Profiling | Next-generation Sequencing |mentioning
confidence: 99%
“…Numerous studies using nextgeneration sequencers have revealed clinically relevant genetic alterations in various tumors, and some researchers have recently advocated the clinical use of next-generation sequencers. [15][16][17][18][19][20] This is the first study to establish a clinical sequencing system for meningioma, which is the most common brain tumor.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction from tumor tissue, sequencing, and bioinformatic analysis at NP has been described previously [6]. In parallel, DNA extraction from blood lymphocytes and NGS are performed to detect germline mutations.…”
Section: Methodsmentioning
confidence: 99%
“…DNA is extracted from both tumor and blood. Targeted NGS is next performed for both sample types using a gene panel of 129 genes known to be involved in brain tumorigenesis or frequently mutated in brain tumor tissue [6].…”
Section: Workflowmentioning
confidence: 99%